Catalysts of corporate value: exploring the interplay between capital structure, company traits, and profitability in the indonesian consumer goods industry (BEI, 2021-2023) - Sarumpaet, Tetty Lasniroha; Bayunitri, Bunga Indah; Lestari, Irene Sukma (Enrichment : Journal of Management, 2024)
This study investigates the interplay between capital structure, company traits, and profitability in the Indonesian Consumer Goods Industry from 2021 to 2023. Through quantitative exploration, 52 companies listed on the Indonesian Stock Exchange were analyzed. The research assesses the impact of capital structure and company characteristics on company value, considering factors like debt usage, profitability, and stock prices. Findings reveal varying influences on company valuation, with implications for financial decision-making and market positioning. The study contributes to understanding the dynamics of corporate value drivers in a specific industry context, offering insights for strategic management and financial planning in the consumer goods sector